Real-Time PCR Assay for the Identification of the Brown Marmorated Stink Bug (Halyomorpha halys) - Dhami, Manpreet K.; Dsouza, Melissa; Waite, David W.; Anderson, Diane; Li, Dongmei (Frontiers in Molecular Biosciences, 2016)
The brown marmorated stink bug, Halyomorpha halys (Hemiptera: Pentatomidae), is a gregarious crop pest that has rapidly spread across the world in the last two decades. It is an excellent hitchhiker species, especially as an over-wintering adult. During this period it is often associated with non-biological commodities such as shipping containers and machinery that travel long distances. Inadequate identification keys and similarity to common species has assisted its spread across Europe, while accurate identification from immature stages or eggs is not possible. We developed a real-time TaqMan PCR assay for the accurate and sensitive detection of the brown marmorated stink bug from all life stages. The assay performance against required diagnostic criterion and within a quarantine framework are described.